2019
DOI: 10.1016/j.plaphy.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen drives plant growth to the detriment of leaf sugar and steviol glycosides metabolisms in Stevia (Stevia rebaudiana Bertoni)

Abstract: Nitrogen drives plant growth to the detriment of leaf sugar and steviol glycosides metabolisms in Stevia (Stevia rebaudiana Bertoni).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 64 publications
1
16
1
Order By: Relevance
“…However, extensive studies illustrated that N fertilization adversely regulates SG concentrations in stevia leaves (Barbet-Massin et al 2015; Karimi and Moradi 2018;Tavarini et al 2015). Our previous study also demonstrated the negative relationships between N fertilization rates and SG concentrations, which were linked to either the dilution effect caused by biomass formation or the soluble sugar accumulation due to N deprivation (Sun et al 2019a). All these findings indicate the dispersal responses of leaf biomass and SG concentrations to N fertilization, which in turn imply that SG productivity can be enhanced by manipulating N fertilization strategies.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…However, extensive studies illustrated that N fertilization adversely regulates SG concentrations in stevia leaves (Barbet-Massin et al 2015; Karimi and Moradi 2018;Tavarini et al 2015). Our previous study also demonstrated the negative relationships between N fertilization rates and SG concentrations, which were linked to either the dilution effect caused by biomass formation or the soluble sugar accumulation due to N deprivation (Sun et al 2019a). All these findings indicate the dispersal responses of leaf biomass and SG concentrations to N fertilization, which in turn imply that SG productivity can be enhanced by manipulating N fertilization strategies.…”
Section: Introductionmentioning
confidence: 64%
“…8' propagated from cuttings were transplanted on June 6. The basic properties of the yellow-brown soil of the experimental field were measured, as pH 6.72 (soil:H 2 O = 1:2.5), organic matter 27.72 mg g −1 , total N 1.528 mg g −1 , Olsen-P 63.97 mg kg −1 , and NH 4 OAc-K 347.72 mg kg −1 (Sun et al 2019a).…”
Section: Plant Materials and Experimental Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenylpropanoid pathway plays an important part in defence and the key regulatory enzyme in this pathway, phenylalanine ammonia_lyase (PAL), is involved in the synthesis of secondary antimicrobial compounds [122]. Generally, genes encoding general phenylpropanoid metabolism such as PAL, cinnamate-4-hydroxylase (C4H) and 4-coumarate: CoA ligase (4CL) are all up-regulated by N deficiency [56,123], while decreased PAL activity has been seen with N fertilization [60,124]. However, discrete responses were reported when challenged with pathogens.…”
Section: Defence-related Enzymesmentioning
confidence: 99%